KINERJA BADAN PERMUSYAWARATAN DESA DALAM PEMBANGUNAN MASYARAKAT DI DESA SAYANG SEDAYU KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Nurul Hadiansyah E.42009006 (FISIP Universitas Tanjungpura Pontianak, 2021)
This study aims to describe and analyze the performance Village Consultative Body carrying out its duties and functions in the Development of village communities in the Sayang Sedayu Village Teluk Keramat sub district Sambas regency. Title of thesis performance issues raised by the Village Consultative Body Sayang Sedayu that is not yet maximal.This study used a qualitative approach, and type of research is descriptive. As for the data collection technique that uses observation, interviews, and documentation. Then for data analysis using data reduction, data display, and conclusion. Research sites in the village of Sayang Sedayu Teluk Keramat sub district Sambas regency. The research subject is Sayang Sedayu BPD members, village chiefs and their village device Sayang Sedayu, community leaders, religious leaders, youth leaders and LPMD. The conclusion of this study is the low performance of the Village Consultative Body Sayang Sedayu in performing its duties and functions.Therefore, the recommendation is expected to BPD Unfortunately Sayang Sedayu to further improve socialization, communication and interaction to the villagers so Sayang Sedayu expected to absorb / accommodate the aspirations of the people, improve coordination among the members of the BPD so that they can work effectively and better, Chairman of BPD should be initiatives in order to increase the motivation of members and government Sambas regency is expected to pay attention to BPD in particular can provide training to members of the BPD's in Sambas regency that BPD members trained and will be able to execute the duties and functions properly. Keywords: Performance, BPD, duties and functions.